A Multidisciplinary Approach in Hadith Studies for Contextual Interpretation - Abdillah, Nanang; Hidayati, Ratna; Ni’am, M. Fathun; Haris, Abd (SAINTIS Publishing, 2025)
The polarization between textual-literalist and contextual-interdisciplinary approaches in understanding hadith in the modern era has become an endless debate that causes a stigma that is not good in Islamic discourse. A multidisciplinary approach in the study of the hadith of the Prophet Muhammad SAW is a need for the interpretation of hadith that is relevant to the challenges of modern society as well as being a mediator of this polarization. This research uses qualitative methods based on library research, content analysis, and critical discourse analysis. Primary data is taken from standard hadith books, while secondary data comes from interdisciplinary literature. The results of the study show that a multidisciplinary approach results in a more comprehensive, adaptive, and contextual understanding of hadith. Linguistic analysis avoids anachronism in the interpretation of terms; sociological and historical approaches place the hadith in social reality and historical chronology; anthropology distinguishes between universal teachings and cultural expressions; philosophy explores universal ethical values; and hermeneutics enriches the process of interpretation according to the dynamics of the times. The contributions of this research include strengthening the integrative methodological framework in the study of hadith, practical relevance for social policy, and the bridge between the classical scientific tradition and the development of contemporary social-humanities sciences. Thus, a multidisciplinary approach not only enriches the scientific treasures of hadith, but also becomes an urgent need to answer the problems of Muslims in the modern era.